Animal Models to Study the Mutational Landscape for Oral Cavity and Oropharyngeal Cancers - Michael T. Spiotto; Matthew Pytynia; Gene-Fu F. Liu; Mark C. Ranck; Ryan Widau (eJournal of Oral Maxillofacial Research)
Objectives: Cancer is likely caused by alterations in gene structure or expression. Recently, next generation sequencing has documented mutations in 106 head and neck squamous cell cancer genomes, suggesting several new candidate genes. However, it remains difficult to determine which mutations directly contributed to cancer. Here, summarize the animal models which have already validated and may test cancer causing mutations identified by next generation sequencing approaches. Material and Methods: We reviewed the existing literature on genetically engineered mouse models and next generation sequencing (NGS), as it relates to animal models of squamous cell cancers of the head and neck (HNSCC) in PubMed. Results: NSG has identified an average of 19 to 130 distinct mutations per HNSCC specimen. While many mutations likely had biological significance, it remains unclear which mutations were essential to, or “drive,” carcinogenesis. In contrast, “passenger” mutations also exist that provide no selection advantage. The genes identified by NGS included p53, RAS, Human Papillomavirus oncogenes, as well as novel genes such as Notch1, Dicer and SYNE1,2. Animal models of HNSCC have already validated some of these common gene mutations identified by NGS. Conclusions: The advent of next generation sequencing will provide new leads to the genetic changes occurring in squamous cell cancers of the head and neck. Animal models will enable us to validate these new leads in order to better elucidate the biology of squamous cell cancers of the head and neck.